The Influence of Staff Promotion on Employee Turnover Intention in Food and Beverage Industry in Nigeria - Chukwu, B.A (Journal of Asian Business Strategy, 2019)
This research examined the influence of staff promotion on employee turnover intention in food and beverage industry in Nigeria. Labor turnover brings destruction to food and beverage industry in Nigeria in the form of direct and indirect costs and profitability. Retention of employee is not easy and is a complex issue and there is no single recipe for retaining employees in a company. Management of food and beverage industry can reduce turnover by considering different preventive measures such as regular and transparent promotion and promotion as at when due. Employees will opt out of the organization if denied promotion. Therefore the objective of the research was to examine the influence of staff promotion on employee turnover intention. This research adopted a survey research instrument through the administration of questionnaires to three hundred and fifty-five (355) staff of the sampled firms. The data for the research was analyzed using descriptive statistics and chi-square. The empirical results from the chi-square analysis showed that promotion as at when due, regular promotion, transparent promotion and when employees are satisfied with promotion has significant influence on employee turnover intention at 5 percent level of significance. Based on the findings of the research, it is recommended that employees should be promoted regularly and as at when due.